2000
DOI: 10.1002/jor.1100180418
|View full text |Cite
|
Sign up to set email alerts
|

Spindle‐shaped cells derived from giant‐cell tumor of bone support differentiation of blood monocytes to osteoclast‐like cells

Abstract: Spindle-shaped cells were established from four giant-cell tumors of bone. When human blood monocytes were co-cultured with these cells, multinucleated giant-cell formation of monocytes was induced. Intriguingly, even when a filter (pore size: 0.45 microm) was interposed between monocytes and the spindle-shaped cells, polykaryocytes also appeared. These multinucleated giant cells were positive for tartrate-resistant acid phosphatase, expressed calcitonin receptor, and showed bone-resorption activity, character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 26 publications
1
37
0
2
Order By: Relevance
“…In addition, Yasuda et al [33] reported that ODF is the mediator of cell-to-cell interaction. In our previous study [22], the cell-to-cell contact between GCTSC and monocytes was mandatory for osteoclastogenesis in vitro. However, it's currently become clear that soluble mediator can drive osteoclastogenesis in the absence of stromal cells, osteoblasts, or other supporting cells [21].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, Yasuda et al [33] reported that ODF is the mediator of cell-to-cell interaction. In our previous study [22], the cell-to-cell contact between GCTSC and monocytes was mandatory for osteoclastogenesis in vitro. However, it's currently become clear that soluble mediator can drive osteoclastogenesis in the absence of stromal cells, osteoblasts, or other supporting cells [21].…”
Section: Introductionmentioning
confidence: 92%
“…After several passages, the multinucleated giant cells and monocytes/macrophage-like round cells progressively disappeared from the cultures, and the proliferating stromal-like cells (GCTSC) only were present after about 4 weeks. Some properties of GCTSC were described previously [22]. These cells were cultured with Dulbecco's minimum essential medium (DMEM) fortified with 5% fetal calf serum (FCS).…”
Section: Giant Cell Tumor-derived Stromal Cells (Gctsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…SC were therefore believed the most likely candidate neoplastic elements of GCT, partly based on their ability to grow both in vitro and in vivo [2,24]. SC exhibit markers of osteogenic differentiation [36,46] and are able to stimulate osteoclasts [34,37] through the ligand for receptor activator of nuclear factor kB (RANKL) [20,28,38], a growth factor essential for the recruitment of osteoclasts by osteoblasts under physiological conditions [18]. In agreement with a putative osteogenic origin of SC, osteoid foci may be found both inside and at the periphery of GCT [8,41], and bone formation, but no evidence of osteoclastogenesis has been observed in immunodeficient mice after subcutaneous injection of GCT tissue or cells [2,24].…”
Section: Introductionmentioning
confidence: 99%
“…The spindle-like stromal cells are the main neoplastic component of GCTB and have been shown to express and secrete a variety of chemotactic factors to enlist pathologic components [12,14,21]. They play an important role in the formation of giant multinucleated cells [7,8,14,17].…”
Section: Microscopic Findingsmentioning
confidence: 99%